Faktor-Faktor yang Mempengaruhi Pelaksanaan Pembangunan Sektor Perkebunan di Desa Leppangeng Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Ardyansyah Ardyansyah (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract Development management at rural territory was influenced by various factors, from the supportive factors to the unsupportive or resistive factors. A region will succeed its development program if those supportive factors can be maximized, while those resistive factors such as minimum infrastructures and low quality human resources can get minimized. This research was done at Leppangeng Village of Pitu Riase District in Sidenreng Rappang regency. The goal was to determine the above factors that influenced the development management in Leppangeng Village particularly at plantation sector. Data collection method used were: (1) field observation, (2) interview, (3) questionnaire, and (4) literature study. Those data were then analyzed using frequency table and percentage method. This research’s population involved thrity-five people, and all accounted as research’s samples. The result showed those factors as followed: (1) commodity or natural resources got 57,14% score as capable to support development progress, (2) farmers’ active role or working spirit got 54,26% score of increase, (3) farmers’ group organization got 62,86% score as affective in plantation sector, and (4) village organization’s role in plantation sector got 54,28% score as affective. Those factors were as mentioned: (1) minimum infrastructures such as transportation and distribution route to fulfill people’s needs got 77,14% score as very affective, and (2) low quality human resources in managing and marketing horticultural results got 80% score as also very affective.